Cerebellar vermis contributes to the extinction of conditioned fear. (14th September 2015) - Utz, A.; Thürling, M.; Ernst, T.M.; Hermann, A.; Stark, R.; Wolf, O.T.; Timmann, D.; Merz, C.J.
Highlights: Re-analysis of a human fMRI study on fear extinction focusing on the cerebellum. The anterior vermis plays a role in the extinction of conditioned fear. The cerebellum is likely part of the neural circuitry underlying extinction of conditioned fear. Abstract: The cerebellum is known to contribute to the acquisition and retention of conditioned motor and emotional responses. Eyeblink conditioning and fear conditioning have been studied in greatest detail. Whereas a considerable number of studies have shown that the cerebellum is also involved in extinction of conditioned eyeblink responses, the likely contribution of the cerebellum to extinction of conditioned fear responses has largely been ignored. In the present study, we analyzed functional brain imaging data (fMRI) of previous work investigating extinction of conditioned fear in 32 young and healthy men, in which event-related fMRI analysis did not include the cerebellum. This dataset was analyzed using a spatial normalization method optimized for the cerebellum. During fear acquisition, an unpleasant electric shock (unconditioned stimulus; US) was paired with one of two pictures of geometrical figures (conditioned stimulus; CS+), while the other picture (CS−) was never paired with the US. During extinction, CS+ and CS− were presented without the US. During the acquisition phase, the fMRI signal related to the CS+ was significantly higher in hemispheric lobule VI in early compared to late acquisition ( p < .05, permutation corrected). During the extinction phase, the fMRI signal related to the contrast CS+ > CS− was significantly higher within the anterior vermis in early compared to late extinction ( p < .05, permutation corrected). The present data show that the cerebellum is not only associated with the acquisition but also with the extinction of conditioned fear.